FAMILY CENTERED CARE IN PATIENTS WITH DIABETIC KETOACIDOSIS AND MULTIPLE ORGAN DYSFUNCTION SYNDROME (MODS) IN THE INTENSIVE CARE UNIT: CASE REPORT - Darmawulan, Nurul; Emaliyawati, Etika (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2023)
Introduction: The presence of family members who are treated in the intensive care unit makes the patient's familyfeel anxiety related to the fear of the death of someone theylove. In dealing with this, family-centered care is used as anapproach that has advantages for families, patients, and healthworkers. This case report aims to describe the family centeredcare towards patient and patient’s family with diabeticketoacidosis and Multiple Organ Dysfunction Syndrome. Method: This study used a case report to describe theintervention in the case. The sample of this study was an adultpatient with diabetic ketoacidosis and MODS who has a family with psychological problems in an intensive care unit. Results: Based on assessment the patient's general conditionwas weak and restless, the level of consciousness undersedation with Ramsay score was 5, the urinalysis found a ketonuria and glucosuria. The patient's family feel guilty, worried, and always asks about the patient's condition whilecrying. The interventions provided with the FCC includeinformation on the patient's condition, treatment plans, andresults after the action is taken, spiritual guidance when thefamily visit time, and provides support. The output obtainedwas the patient's family feels calmer and satisfied with thehealth services provider. Conclusions: The implementation of the FCC can decreaseanxiety and increase health care satisfaction, but theimplementation can be challenged so that it is necessary todevelop the FCC program in the ICU which requiresinvolvement and input from all parties.